A Simple Low Jitter Wireless Triggering and Unidirectional Communication System - Depold, Andreas; Dorn, Christian; Weigel, Robert; Lurz, Fabian (2023 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2023, 2023)
This paper presents a simple, low-cost synchronization system based on a Sub-GHz of-the-shelf transceiver. It is intended for synchronization between a base station and mobile measurement system for search and rescue applications. Time critical scheduling information can be transmitted together with triggering pulses. Additionally, during off time bulk data can be transmitted. The system allows for triggering with a known latency and with a standard deviation below 200 ns.
Created from Fastlane, Scopus look-up
Keywords: triggering; wireless sensors; wireless synchronization